Repellent Plants and Seed Treatments for Organic Vegetable Soybean Production - Sandra Arifin Aziz; Agus Yudhi Pardiyanto; Meity Suradji Sinaga (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
The research was conducted to study the effect of repellent plants and seed treatments on growth and production of organically grown vegetable soybean. The experiment was carried out at Cikarawang Research Station, Bogor, from September 2005 to May 2006. The organic experiment was arranged in a split plot design using four species of companion plants as repellent plants, i.e. Tagetes erecta, Cymbopogon nardus, Ocimum gratissimum, Tephrosia vogelii, and without repellent plants as the main plot, and seed treatments i.e. galangal oil, Pseudomonas fluorescens, and without seed treatments as sub plot using 3 replications and conventional system (using pesticides) as control. Plants grown under conventional system had a greater fresh pod weight (6.7 kg. 10 m-2) than those in organic system (4.80-5.79 kg. 10 m-2), a lower insect infestation (19.17, 22.92 and 32.50%) and disease prevalence (9.17, 11.42 and 14.42%), at 6, 7 and 8 Week After Planting (WAP) respectively, than the organic system. In the organic experiment, the use of O. gratissimum as repellent plants resulted in a significantly lowest empty pod per plant (0.79 g). T. erecta and O. gratissimum without seed treatment, P. fluorescens without repellent plants, and T. vogelii with galangal oil seed treatment has the significant lowest insect infestation at 6 WAP of 20.67, 23.00, 26.67 and 27.33%, respectively. An organic system using repellent plants had a significantly lower insect infestation at 8 WAP (35.67-40.33%, O. gratissimum being the lowest) than without repellent plants (50.56%). Seed treatments on organic system had the lower disease prevalence at 8 WAP (33.87% on P. fluorescens and 35.47% on galangal oil) than without seed treatments (37.73%). Number of root nodules (11.6-16.7 to 7.8) and root nodules dry weight (0.068- 0.101 to 0.040 g) of the organic system were greater than the conventional system. Soybean without repellent plants had a greater number of harvestable plants (137.3), but it was fewer than the conventional system (158.3)